Magnetic-nanoparticles-based fluorescent immunoassay for individual and simultaneous determination of dichlorvos and paraoxon in milk - Marina Yaneva; Yavor Ivanov; Nikola Todorov; Tzonka Godjevargova (Food and Agricultural Immunology, 2018)
A sensitive and rapid magnetic-nanoparticles-based fluorescent immunoassay (MNPs-FIA) for individual and simultaneous determination of dichlorvos (DDVP) and paraoxon in untreated raw milk was developed. The conjugates DDVP–cBSA (cationized bovine serum albumin) and paraoxon–BSA (bovine serum albumin) were labeled by fluorescent dyes. The optimal amount of immobilized polyclonal anti-DDVP and anti-paraoxon antibodies on MNPs (0.375 mg Ab-MNPs) and optimal concentrations of DDVP–cBSA–FITC (18 µg/mL) and paraoxon–BSA–FITC (22 µg/mL) for MNPs-FIA were determined. The calibration curves of individual and simultaneous immunoassays of DDVP and paraoxon were investigated. The IC50 value of the individual paraoxon assay in raw cow’s milk was 60 ng/mL and linear range 2–300 ng/mL. The IC50 value of the individual DDVP assay was 70 ng/mL and linear range 5–300 ng/mL. The IC50 values of the paraoxon and DDVP (100 and 120 ng/mL respectively) in simultaneous assay were higher than those of the individual ones, and their linear ranges were 10–400 ng/mL.